Peran Framing dan Branding dalam Penguatan Citra Desa Paokmotong sebagai Sentra Perdagangan di Provinsi Nusa Tenggara Barat: The Role of Framing and Branding in Strengthening the Image of Paokmotong Village as a Trade Center in West Nusa Tenggara Province - Hidayati, Lilik; Dayulia, Hilmayana Irma; Fajrianti, Isnaini; Oktavianty, Neni; Saputra, Galu; Kholidi, Ahmad Isfan; Umami, Muhammad Trisna; Maulana, Tegar; Komalasari, Nur; Ariyanti, Desi; Fadilah, Nurul (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Paokmotong Village has great potential as a trading center in the Province of West Nusa Tenggara (NTB). However, strengthening the village's image as a trading center still faces various challenges, including in the aspects of branding and framing. This research aims to analyze the role of branding and framing strategies in building a positive image of Paokmotong Village as a trade center. With a qualitative approach, this activity examines how the application of branding and framing elements can enhance the village's competitiveness in the trade sector. The research results show that branding strategies through visual identity and digital marketing have proven effective after the installation of market maps, content creation socialization, and digital marketing training in enhancing the village's image as a trade center in NTB Province. Meanwhile, the framing strategy through positive news coverage, historical narratives, and publications supports the creation of a positive perception of Paokmotong Village among the community. With the right combination of branding and framing, Paokmotong Village can be further strengthened as a modern, competitive, and sustainable trade center.